Reevaluation of reference values for bone marrow differential counts in 236 healthy bone marrow donors - Parmentier, Stefani (Ann Hematol, 2020)
Despite the increasing role of molecular markers, differential counts and morphology of hematopoietic cells in the bone marrow (BM) remain essential diagnostic criteria in hematological diseases. However, the respective reference values for BM myelogram commonly used came from small series with limited numbers of healthy individuals. We evaluated the myelograms of 236 healthy individuals who underwent unrelated bone marrow donation. Health check-ups were performed 4 weeks prior to harvest. Samples for this study, taken from the first aspiration, were stained according to the standard Pappenheim method. Three experienced investigators assessed cellularity, megakaryopoiesis, and differential counts independently. The median donor age was 31 (range 18–51) years. Predonation tests did not reveal any relevant morbidity. Thirty-seven out of 42 hypocellular marrow samples were from younger donors up to 39 years. Content of megakaryocytes was normal in 210 specimens (89%). Gender and body mass index had significant impact on hematopoiesis, whereas age had not. The number of erythroblasts was higher (about 32%) and the proportion granulopoiesis slightly lower (about 50%) compared with previous studies. Differential counts showed also some differences with respect to individual maturation stages in these lines. Interrater comparisons showed greater reliability for the assignment of cells to the different hematopoietic cell lines than for single-cell diagnoses. This study largely confirms the results for cell counts in normal human bone marrow available from previous reports and provides some insights into factors that affect individual cell populations. It also reveals substantial variability among even experienced investigators in cytological diagnoses.